Numerical models to simulate heat and mass transfer at sharp interfaces in nucleate boiling. (17th November 2018) - Perez-Raya, Isaac; Kandlikar, Satish G.
Abstract: This work describes a simulation technique for nucleate boiling that considers mass transfer with interfacial temperature gradients and a sharp interface. Interpolation functions estimate the temperature at points located in a direction normal to the interface. A linear temperature profile at the interface interpolates the temperature of the interface-cells. An interface-cells segregation algorithm avoids the interface smearing. Simulations with water at 6.2 K wall superheat show good agreement with the available experimental data on bubble growth rate. Results reveal large heat transfer coefficients over a 200 μm region near the interface. Analysis of the wall shear stress indicates an influence region around the bubble base of two-times the departure bubble diameter.